Applicability of conservation agriculture for climate change adaptation in Rwanda’s situation - Kabirigi, M.; Musana, B; Ngetich, Felix K.; Mugwe, J.; Mukuralinda, Athanase; Nabahungu, N.L. (Academic Journals, 2015)
Improving food security and environmental conservation should be the main targets of innovative farming systems. Conservation agriculture (CA), based on minimum tillage, crop residue retention and crop rotations has been proposed against poor agricultural productivity and soil degradation. This paper discusses the applicability and potential benefits of CA in Rwanda under the unfolding climate change scenario. The potential and benefits from CA may vary with rainfall regime. In high rainfall areas (For example North and West of Rwanda), the soils are susceptible to soil erosion and face fertility decline while in low rainfall areas (For example East of Rwanda) crops fail due to sub-optimal water use efficiency. Furthermore, low organic carbon content lower fertilisers response and government targets of increasing production through Crop Intensification Program, is limited. It has been shown that CA can: Reduce soil loss from 35.5 to 14.5 t/ha/year, have 50-70% greater infiltration and increase 42% of organic carbon. Long term analysis using Agricultural Production System Simulator showed that CA can increase yield from 3.6 to 4.4t/ha in areas having >770 mm. Based on the evidence from regional research, CA has a good potential for climate change adaptation in both high and low rainfall areas of Rwanda. However, decreased yield observed in high rainfall areas, increased labour requirements when herbicides are not used and lack of mulch due to priority given to feeding of livestock constrained CA adoption. We conclude that there is a need for critical assessment under which ecological and socio economic conditions CA is suited for smallholder farming in Rwanda.